Comparison of video laryngoscope and direct laryngoscope for endotracheal intubation across different body mass index categories: A prospective study - Gulay Esen; Arzu Acikel (Medicine Science)
The aim is to compare video laryngoscopy (VL) and Macintosh blade direct laryngoscopy according to the intubation difficulty scale (IDS) in patients with ASA 1 and Mallampati score I (C-MAC-D blade) according to body mass index (BMI). A total of 180 patients aged 18-70 years, scheduled for elective surgery under general anesthesia with ASA 1-2, Mallampati score I, and BMI>18 kg/m² were included. DL and VL were performed in 50% of patients. Patients were randomly assigned to six groups based on BMI and laryngoscopy type. During intubation, data on the number of tubes used, number of anesthetists attempting intubation, number of alternative techniques employed, C-L score (C-L), laryngoscopy suspension power, application of external pressure, and vocal cord imaging were recorded, and IDS was calculated. Notable variations were detected in mouth opening, thyromental distance, and C-L and IDS levels across different laryngoscopy methods. Patients in the VL group exhibited a greater frequency of mouth opening of [Med-Science 2024; 13(4.000): 921-9]